La gestion des déchets urbains au Liban entre politiques publiques et privées - Nada Chbat (Projets de Paysage)
This article analyzes the Lebanese situation concerning the management of the urban waste. The rationalized management of the waste in Lebanon is hindered by three obstacles : the first is institutional (distribution of the roles between the ministries, the public sector, and the private sectors, the NGO and inhabitants). The second obstacle is financial (the necessary means to finance this sector) and the third is social (the localization of the waste/discharges and the contrasted nature of their social representations : from fear to utility). The establishment of sustainable and satisfactory urban cleanliness supposes, beyond the strictly technical questions, first an awareness of the necessity of new cooperation between public and private actors.